The Student of a Pedagogical College: the Attitude towards Education and Professional Plans - Vladimir Sobkin; Olga Tkachenko; Anna Fedjunina (Voprosy obrazovaniya / Educational Studies Moscow, 2010)
The paper is based on the data of a questionnaire poll that was conducted by the Center of Education Sociology of the Russian Academy of Education in 2003. Attention is given mainly to the study of the motivation to obtain a higher education, specifics of the students' attitude to the quality of their education (whether it is sufficient, basic, systematic, modern), students' involvement in research, and plans regarding future professional activity. Gender and age differences are considered; opinions of students from pedagogical and technical colleges are com_ pared. Factor analysis of the obtained empirical material was specifically carried out to elucidate the structural characteristics of motivation changes in male and female students at pedagogical and technical universities. It is shown that principal changes in the attitude towards the acquisition of higher education take place at the beginning of the 3rd year. They are connected with the increase of the role of education as a personality development factor. This result not only brings the authors to conclusions about the specifics of development of learning activities at the higher education level, but also demonstrates that a certain «studying crisis» takes place. This crisis manifests itself both in a re-estimation of the quality of the education acquired and in a decreased orientation towards the professional activities related to it.